Nanotechnology and Ethical Governance in the European Union and China: Towards a Global Approach for Science and Technology - Dalton-Brown, Sally (Springer, 2015)
This book addresses questions surrounding the feasibility of a global approach to ethical governance of science and technology. The emergence and rapid spread of nanotechnology offers a test case for how the world might act when confronted with a technology that could transform the global economy and provide solutions to issues such as pollution, while potentially creating new environmental and health risks. The author compares ethical issues identified by stakeholders in China and the EU about the rapid introduction of this potentially transformative technology – a fitting framework for an exploration of global agency.